Antihistamine updosing in chronic urticaria – is there enough evidence?. (1st December 2016) - Weller, K.; Maurer, M.
Abstract: Linked Article: Guillén‐Aguinaga et al. Br J Dermatol 2016; 175 :1153–1165 .